2017
DOI: 10.1002/jor.23722
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic elution from acrylic bone cement loaded with high doses of tobramycin and vancomycin

Abstract: Two-stage revision treatment of prosthetic joint infection (PJI) frequently employs the use of a temporary bone cement spacer loaded with multiple antibiotic types. Tobramycin and vancomycin are commonly used antibiotics in cement spacers, however, there is no consensus on the relative concentrations and combinations that should be used. Therefore, the purpose of this study was to investigate the influence of dual antibiotic loading on the total antibiotic elution and compressive mechanical properties of acryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 41 publications
3
51
1
Order By: Relevance
“…Penner et al [8] tested vancomycin and tobramycin release, finding that elution of vancomycin and tobramycin was 103% greater and 68% greater in dual combinations, respectively. Similar results were presented by Slane et al [9], who found that mixing tobramycin with vancomycin resulted in significantly higher elution of both antibiotics (P < .001), additionally observing a synergistic effect on tobramycin elution with the addition of vancomycin. A study by Klekamp et al [20] discovered that vancomycin decreased the elution of tobramycin, while tobramycin did not have a reciprocal effect.…”
Section: Lowest Level Of Evidence Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…Penner et al [8] tested vancomycin and tobramycin release, finding that elution of vancomycin and tobramycin was 103% greater and 68% greater in dual combinations, respectively. Similar results were presented by Slane et al [9], who found that mixing tobramycin with vancomycin resulted in significantly higher elution of both antibiotics (P < .001), additionally observing a synergistic effect on tobramycin elution with the addition of vancomycin. A study by Klekamp et al [20] discovered that vancomycin decreased the elution of tobramycin, while tobramycin did not have a reciprocal effect.…”
Section: Lowest Level Of Evidence Studiessupporting
confidence: 89%
“…Vancomycin is the most common antibiotic added to aminoglycoside ALCs and improves the spectrum of coverage to include methicillin-resistant Gram positive organisms [7]. A secondary effect of these combinations is a higher and longer lasting elution of both drugs [8,9]. This synergism between vancomycin and aminoglycosides has been recognized and extensively studied for decades.…”
mentioning
confidence: 99%
“…The dose of antibiotics contained in the bone cement had been regarded as an important factor affecting the elution or mechanical strength of antibiotics in experimental setting [22]. In in vitro experiments, greater amount of antibiotics loaded bone cement usually showed higher concentration of eluate in early phase; however, the gap of concentration between different doses of contained antibiotics has been narrowed toward late phase [9,10,19,22,23]. In most of the experimental studies, a similar pattern of elution was observed, initially released in large amounts and then sharply decreased [19,22e25].…”
Section: Discussionmentioning
confidence: 99%
“…There were several experiments to assess whether the addition of antibiotics to bone cement reduces the mechanical properties depending on doses of antibiotics [32,34e36]. Related to eluting capacity of antibiotics and mechanical strength of ALBC, superficial characteristics and porosity of bone cement is considered as important factors controlling the release kinetics of antibiotics and supporting the microstructures of ALBC [22,37,38]. Therefore, a number of variables that influence the porosity of bone cement during production of ALBC had been investigated [22,33,38e40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation